Perspectives of Caring for Older Persons: A Scoping Review - Ignatius Chida; Manohar Pawar; Ndungi Mungai (SAGE Publishing, 2024)
In this article we explore caring practices for older persons from multiple care perspectives related to organizing home-based care. We employed a scoping review method and searched 5 electronic database using relevant key words and identified 62 articles for codebook thematic analysis. Our analysis identified 6 key themes in older people's care: gender issues; socio-economic status; psychological; cultural issues; elder abuse; and legal, ethical, and human rights concerns. Findings show that despite notable research progress made in recent years on home-based care for older people, research gaps still exist. Researchers and practitioners are encouraged to consider viewing home-based care for older people from multiple perspectives to ensure a holistic understanding of an individual's needs and circumstances and organize care accordingly. Future research and practice should seek to understand the lived experiences of care givers and receivers from multiple care perspectives, to help inform responsive and effective home-based care policies and programs.